Reflections on Japan’s participation in negotiations of the global plastic pollution instrument under international environmental law - Xu, Qi; Zhang, Mengxue; Guo, Peng (Frontiers in Marine Science, 2023)
International negotiations towards a legally binding instrument on the global plastic pollution have obtained wide-ranging attention from international community. It is revealed that Japan has taken a conservative but proactive stance during negotiations. This study overviews Japan’s current legal framework on the management of plastic pollution including land and the sea. On this basis, the paper then analyzes Japan’s stance in the negotiations to examine the issues that are of most concern to Japan in international cooperation towards ending plastic pollution. It will further analyze Japan’s views on the legally binding instrument’s framework, operational mechanism and key components from the perspective of international environmental law. And it will also summarize Japan’s specific claims and objectives in the negotiations, and provide an evaluation of Japan’s stance.